Simulation of Airway Management for the Pediatric Resident - Suzanne Friedman; Meghan Tozzi; Ashley Siems; Abigail Carey; Scott Moerdler; Sheemon Zackai (Association of American Medical Colleges, 2014)
Abstract The purpose of this resource is to provide interns and residents with the opportunity to assess and manage respiratory distress in a simulated patient encounter. The direct goal is to use the simulator as a means to teach residents about airway management. This session can be used as part of a simulation curriculum or on its own using the high-fidelity simulator. In this resource, the residents engage in a hands-on simulation activity; a brief and interactive slide presentation follows this to discuss the topic in detail; and then residents engage in a second simulation activity to practice their learned knowledge and skills and then debrief the case. This submission has been used within the pediatric residency program for the past 2 years, with both small and large groups. Residents and interns have frequently reported that they felt more prepared for common pediatric airway conditions that occur after this simulation session.